Evaluasi Rasionalitas Penggunaan Antidiabetes Oral pada Pasien Diabetes Melitus Tipe 2 Rawat Inap di Rumah Sakit Nasional di Dili - Putu Dian Marani Kurnianta; Gracia Isabel Baptista Soares; Anak Agung Ngurah Putra Riana Prasetya; Agustina Nila Yuliawati (Jurnal Farmasi Indonesia, 2022)
Among several types of diabetes mellitus (DM), type-2 DM seemed to demonstrate the highest prevalence. Appropriate management in type-2 DM should follow rational use of antidiabetic agents to prevent any unfavorable impacts. In fact, due to the limited guidelines and medication resources, medication process for patients with type-2 DM has not been evaluated in Timor-Leste, especially at a national hospital in Dili. This was the first study which aimed to evaluate the use of oral antidiabetic agents (OAD) in hospitalized patients with type-2 DM at a national hospital, Dili Timor-Leste.This study was conducted retrospectively under cross-sectional design to describe the rational drug use evaluation based on indicators: right patient, right dose, right indication, right drug, and cautious to adverse events according to guideline from American Diabetes Association (2020). The included patients were diagnosed as type-2 DM, hospitalized during year 2020, and received OAD. Data were calculated (%) for each indicator of rational drug use.A total number of 83 hospitalized patients with type-2 DM at a national hospital in Dili had taken metformin (62.65%), gliclazide (12.15%), and combination of both metformin and gliclazide (22.89%), respectively. The evaluation results of OAD use according to ADA guideline comprised of right indication 100%, right patient 100%, right drug 72.28%, right dose 100%, and cautious to adverse events 93.7%. Despite favorable results in rational medication, enhancement for limitation of OAD use at a national hospital in Dili, Timor-Leste is compulsory.